Understanding metacognition: concepts supporting employee learning and growth. Issue 6 (13th August 2018) - Lyons, Paul R.; Bandura, Randall P.
Abstract : Purpose: The purpose of this paper is to express metacognitive functioning in general terms and to explain how it influences employee learning/knowledge acquisition, self-regulation, engagement and growth mind-set. Design/methodology/approach: The authors provide a viewpoint grounded on a review of recent research regarding the regulation of learning on-the-job. Concepts are expressed in a direct manner for the use of human resource practitioners and managers. Findings: Metacognition is mental work that helps one to regulate and improve his/her learning. The authors find that there are ways for human resource practitioners and/or managers to assist employees improve their learning practices that ultimately influence work activities and outcomes. Originality/value: Metacognition is not a scientific mumbo-jumbo; it represents how one learns to learn. In organizations, it is important to understand how a typical employee may improve her/his learning processing and learning outputs. Authors suggest that practitioners and managers attain some understanding of metacognition and how one may stimulate improved learning processing in employees.